2022
DOI: 10.3389/fmicb.2022.952110
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and accessory genome diversity reveal insight into the evolutionary history of Streptococcus dysgalactiae

Abstract: Streptococcus dysgalactiae (SD) is capable of infecting both humans and animals and causing a wide range of invasive and non-invasive infections. With two subspecies, the taxonomic status of subspecies of SD remains controversial. Subspecies equisimilis (SDSE) is an important human pathogen, while subspecies dysgalactiae (SDSD) has been considered a strictly animal pathogen; however, occasional human infections by this subspecies have been reported in the last few years. Moreover, the differences between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The tested strains isolated from animals came from cattle and were assigned to the SDSD subspecies. However, strains infecting companion animals sometimes have been identified as SDSE [ 33 ]. Our studies have shown that the resistance of this species to drugs used in human therapy applies to both subspecies.…”
Section: Resultsmentioning
confidence: 99%
“…The tested strains isolated from animals came from cattle and were assigned to the SDSD subspecies. However, strains infecting companion animals sometimes have been identified as SDSE [ 33 ]. Our studies have shown that the resistance of this species to drugs used in human therapy applies to both subspecies.…”
Section: Resultsmentioning
confidence: 99%
“…Using accessory genomes in disease epidemiology proved to be effective because gene turnover (i.e., gain and loss) occurs faster than the accumulation of mutations in A. baumannii over very short microevolutionary scales ( 33 ). In Streptococcus dysgalactiae , the distinction between its two subspecies and their ability to adapt to either human or bovine host lie in a specialized accessory genome characterized by the presence of specific surface-protein virulence determinants and carbohydrate metabolic functions ( 34 ). In S. aureus from different vertebrate hosts, accessory gene pools consisting of host-specific genes promote adaptive evolution after host-switching events ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of S. dysgalactiae strains into subspecies was not performed because the taxonomy of S. dysgalactiae remains unclear. Recent studies indicate that S. dysgalactiae may be segregated into two distinct groups: one includes only human strains, while the other includes animal strains of swine, canine and equine origin, as well as more phylogenetically distinct bovine strains [ 37 ]. Most S. dysgalactiae isolates in this study belonged to Lancefield group C, as is consistent with previous reports [ 7 , 38 ], but some isolates belonged to group A.…”
Section: Discussionmentioning
confidence: 99%